2001
DOI: 10.1007/pl00011306
|View full text |Cite
|
Sign up to set email alerts
|

Cleaner energy production with integrated gasification combined cycle systems and use of metal oxide sorbents for H2S cleanup from coal gas

Abstract: World primary energy demand increases with increases in population and economic development. Within the last 25 years, total energy consumption has almost doubled. In order to meet this demand, research into new sources of energy as well as improving the efficiency of energy production technologies is being carried out. In both cases, the production of clean energy is very important because of environmental concerns and regulations. Integrated gasification combined cycle (IGCC) technology seems to be one of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…1(b) and (c)). In previous studies, it was found that solid sorbents based upon Mn have promising desulfurization potential (Westmoreland and Harrison, 1976;Atimtay, 2001). Laboratory scale experiments have also been conducted, and Mn-based sorbents were proved to have high desulfurization performance (Bakker et al, 2003;Ko et al, 2005).…”
Section: Thermodynamic Screeningmentioning
confidence: 99%
“…1(b) and (c)). In previous studies, it was found that solid sorbents based upon Mn have promising desulfurization potential (Westmoreland and Harrison, 1976;Atimtay, 2001). Laboratory scale experiments have also been conducted, and Mn-based sorbents were proved to have high desulfurization performance (Bakker et al, 2003;Ko et al, 2005).…”
Section: Thermodynamic Screeningmentioning
confidence: 99%
“…However, the growth in energy production need not take place to the detriment of the environment, so that strict regulations on pollutant emissions have been imposed around the world. An integrated gasification combined cycle (IGCC) systems are being advanced today, due to their higher thermal efficiency and superior environmental performance and economics, compared to conventional plants [293]. The development of these systems depends on the ability to remove sulphur compounds, mainly H2S, from the coal gas.…”
Section: Desulphurization Of Hot Coal Gasmentioning
confidence: 99%
“…Previous literatures have reported on sorbent based upon manganese having promising desulfurization potential (Westmoreland and Harrison, 1976;Atimtay, 2001). Laboratory scale experiments were also conducted showing that Mn-based sorbents had high desulfurization performance (Bakker et al, 2003;Ko et al, 2005).…”
Section: Introductionmentioning
confidence: 99%